2017
DOI: 10.1177/0033294116687123
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Writing Anxiety and Motivation on EFL College Students’ Self-Evaluative Judgments of Corrective Feedback

Abstract: Feedback is regarded as a way to foster students' motivation and to ensure linguistic accuracy. However, mixed findings are reported in the research on written corrective feedback because of its multifaceted nature and its correlations with learners' individual differences. It is necessary, therefore, to conduct further research on corrective feedback from the student's perspective and to examine how individual differences in terms of factors such as writing anxiety and motivation predict learners' self-evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 44 publications
4
29
0
Order By: Relevance
“…The quality of notice (Qi & Lapkin, 2001) and the extensiveness of learner engagement may contribute to writing outcomes. Furthermore, Tsao et al (2017) found that learners' intrinsic motivation and anxiety about writing tests and making mistakes could predict their self-evaluative judgments of teacher and peer WCF. Student preferences for teacher feedback either on local or on global errors were also discovered in previous studies (Hedgcock & Lefkowitz, 1994;Horbacauskiene & Kasperaviciene, 2015).…”
Section: Literature Review Learner Engagement With Wcf In L2 Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of notice (Qi & Lapkin, 2001) and the extensiveness of learner engagement may contribute to writing outcomes. Furthermore, Tsao et al (2017) found that learners' intrinsic motivation and anxiety about writing tests and making mistakes could predict their self-evaluative judgments of teacher and peer WCF. Student preferences for teacher feedback either on local or on global errors were also discovered in previous studies (Hedgcock & Lefkowitz, 1994;Horbacauskiene & Kasperaviciene, 2015).…”
Section: Literature Review Learner Engagement With Wcf In L2 Writingmentioning
confidence: 99%
“…The 10 items were adapted from Tsao et al (2017) to assess learners' engagement with teacher and peer WCF due to its focus on five major types of errors: (1) technical details (i.e., contractions, capitalization, and punctuation), (2) grammatical rules, (3) vocabulary/collocations, (4) content, and (5) organizational structure. The first three items in each scale were related to local errors (i.e., technical details, grammar, and vocabulary/collocations), and the other two were related to global errors (i.e., content, and organizational structure).…”
Section: The Learner Engagement With Written Corrective Feedback Scalementioning
confidence: 99%
“…Besides that, writing skill acts for the most demanding skill since it can only be controlled across learning in comparison with the other three skills: speaking, reading and listening (Zailaini et al, 2015). Some academics contended that writing is not only seen as a cognitive activity, yet it is also perceived as an emotional activity (Pajares & Valiante, 1997;Tsao et al, 2017). Consequently, it is highly connected with some affective variables, for instance, debilitating writing anxiety, facilitating writing anxiety and writing achievement motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is highly connected with some affective variables, for instance, debilitating writing anxiety, facilitating writing anxiety and writing achievement motivation. These aforementioned affective variables are deemed contributing factors of learning and outcome (Cheng, 2004;Tsao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation